2022
DOI: 10.3390/plants11111389
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High-Affinity Potassium Transporter IbHKT-like Gene Enhances Low–Potassium Tolerance in Transgenic Roots of Sweet Potato (Ipomoea batatas (L.) Lam.)

Abstract: The high-affinity potassium transporters (HKT) mediate K+-Na+ homeostasis in plants. However, the function of enhancing low-potassium tolerance in sweet potato [Ipomoea batatas (L.) Lam.] remains unrevealed. In this study, a novel HKT transporter homolog IbHKT-like gene was cloned from sweet potato, which was significantly induced by potassium deficiency stress. IbHKT-like overexpressing transgenic roots were obtained from a sweet potato cultivar Xuzishu8 using an Agrobacterium rhizogenes-mediated root transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…K + transporters and K + channels are important factors that contribute to K + uptake and translocation. Our previous studies identified and analyzed the K + transporter and channel gene families in sweetpotato and verified that IbAKT1 and IbHKT1 function in K + absorption [ 8 , 28 ]. HAK5, belonging to the high-affinity uptake system, is the only one capable of supplying K + to the plant under very low external K + conditions [ 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…K + transporters and K + channels are important factors that contribute to K + uptake and translocation. Our previous studies identified and analyzed the K + transporter and channel gene families in sweetpotato and verified that IbAKT1 and IbHKT1 function in K + absorption [ 8 , 28 ]. HAK5, belonging to the high-affinity uptake system, is the only one capable of supplying K + to the plant under very low external K + conditions [ 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…In addition to root morphology, research on the mechanism of low K + tolerance in plants mainly focuses on K + channel proteins (Shaker K + channel family) and K + transporters (KUP/HAK/KT potassium transporter family) in roots. In sweetpotato, it has been reported that IbAKT1 [33] and IbHKT-like [34] may play important roles in the regulation of K + deficiency tolerance in sweetpotato. Whether they have different roles in the two varieties in this experiment, regarding their interaction with root morphology and IAA, is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also been conducted to identify the key genes induced by other pathogens or abiotic stress tolerance in sweetpotatoes [19][20][21][22][23]. IbBAM1.1, one of the β-amylase genes, acts as a positive regulator to enhance drought and salt stress resistance by regulating the level of osmoprotectants to balance osmotic pressure and activate the scavenging system to maintain reactive oxygen species (ROS) homeostasis in plants [22].…”
Section: Introductionmentioning
confidence: 99%